2009
DOI: 10.1016/j.jvs.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin promotes arteriogenesis and hemodynamic recovery in a rabbit hindlimb ischemia model

Abstract: In a rabbit hindlimb ischemia model, thrombin promoted the formation of large collateral vessels and improved the perfusion of distal ischemic tissue. These results provide new insights in understanding the involvement of thrombin in vascular formation and point to a novel role of thrombin in arteriogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…Administration of thrombin, trypsin or a PAR2-derived synthetic peptide enhances blood flow recovery, but only for thrombin it is known that it increases collateral formation after induction of hind limb ischemia by excision of the femoral artery [19], [20]. While in these studies collateral formation was dependent on supraphysiological concentrations of the PAR1-agonist thrombin and detailed data on collateralization upon PAR2 activation is missing, direct evidence for a physiological role of PAR1 and PAR2 in collateral formation is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of thrombin, trypsin or a PAR2-derived synthetic peptide enhances blood flow recovery, but only for thrombin it is known that it increases collateral formation after induction of hind limb ischemia by excision of the femoral artery [19], [20]. While in these studies collateral formation was dependent on supraphysiological concentrations of the PAR1-agonist thrombin and detailed data on collateralization upon PAR2 activation is missing, direct evidence for a physiological role of PAR1 and PAR2 in collateral formation is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Arteriogenesis is essential to the re-establishment of an adequate blood supply to ischemic organs and tissues. It was previously thought that compared to angiogenesis (capillary formation), arteriogenesis is a distinct process based on the remodeling and maturation of pre-existing arterioles and arteries, 1) characterized by proliferation of pre-existing smooth muscle cells (SMCs), endothelial cells (ECs), or their resident precursors. 2) Recent reports that arteriogenesis is augmented by bone marrow mononuclear cells [3][4][5] and endothelial progenitor cells suggest involvement in arteriogenesis of not only proliferation of resident cells, but also migration and proliferation of circulating stem cells/precursor cells.…”
mentioning
confidence: 99%
“…Several studies have demonstrated arterogenisis as the dominant mode of native vascular remodeling in young otherwise healthy subjects. [23][24][25] Of note, extensive collateralization was seen on arteriography in animals subjected to ligation in this study, which undoubtedly contributed to recovery after a vascular injury. This observation corroborates findings by others who have described decreasing collateral resistance 2 weeks after femoral artery occlusion in pigs.…”
Section: Figmentioning
confidence: 50%